2015
DOI: 10.7150/jca.13176
|View full text |Cite
|
Sign up to set email alerts
|

MiR-182 Is Associated with Growth, Migration and Invasion in Prostate Cancer via Suppression of FOXO1

Abstract: Background: MicroRNA (miRNA) have been shown to regulate gene expression in many cancers. MiR-182 has recently been found to be prognostic for patients treated with radical prostatectomy for prostate cancer. We sought to assess miR-182 as a prognostic marker and understand its role in prostate cancer progression and metastasis.Methods: We analysed miR-182 expression among 147 men treated for prostate cancer using biochemical recurrence and metastasis as the endpoints. We examined miR-182 expression in prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 20 publications
1
52
1
Order By: Relevance
“…Previous studies have revealed that decreased transcriptional expressions and activities of FOXO1 and FOXO3a were correlated with increasing tumor grade and associated with cancer progression . In addition, both FOXO1 and FOXO3a are involved in the regulation of cell apoptosis, proliferation and invasion in PCa . However, the precise molecular mechanism of the abnormal expression of FOXO remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that decreased transcriptional expressions and activities of FOXO1 and FOXO3a were correlated with increasing tumor grade and associated with cancer progression . In addition, both FOXO1 and FOXO3a are involved in the regulation of cell apoptosis, proliferation and invasion in PCa . However, the precise molecular mechanism of the abnormal expression of FOXO remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In addition, both FOXO1 and FOXO3a are involved in the regulation of cell apoptosis, proliferation and invasion in PCa. 9,[14][15][16][17][18][19][20] However, the precise molecular mechanism of the abnormal expression of FOXO remains unclear.…”
mentioning
confidence: 99%
“…It has been found that miR‐182 is upregulated in various cancers, including prostate cancer (Wallis et al, ; Yan et al, ), glioblastoma (Kouri et al, ), hepatocellular carcinoma (Du et al, ). Moreover, miR‐182 is capable of promoting cellular differentiation by regulating the expression of snail family transcriptional repressor 2 ( SNAI2 ), thereby inducing the mesenchymal‐to‐epithelial transition (Qu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between miR‐182 and FOXO1 had been studied in many physiological processes and diseases. For instance, miR‐182 could act to increase prostate cancer proliferation, migration, and invasion through suppression of FOXO1 (Wallis et al, ), whereas the miR‐182/ FOXO1 pathway induced cell apoptosis and inhibited osteoblast proliferation and differentiation (Kim et al, ), which might be a valuable axis in the development of further therapeutic interventions. The effect of FOXO1 in hepatic fibrosis has also been investigated in previous studies, and it has been confirmed that FOXO1 could regulate proliferation and transdifferentiation of HSCs (Adachi et al, ).…”
Section: Introductionmentioning
confidence: 99%